Improving a long-acting reversible contraception usage by understanding client perspectives (Medical Journal of Indonesia, 2020)
BACKGROUND Despite the limited use of long-acting reversible contraception (LARC) in Indonesia, they have proven to be cost-effective in family planning programs. This study was aimed to identify the elements of ideas and views that people hold and their association with the use of LARC (intrauterine devices and implants) as a means of improving its utilization in Nusa Tenggara Barat (NTB) Province, Indonesia. METHODS Data were derived from the Improving Contraceptive Mix Methods survey of 6,384 respondents in Bima District, Central Lombok, and North Lombok, NTB Province, in 2015. Confirmatory factor analysis was used to identify suitable elements of 19 variables and generate three ideation elements on attitude, knowledge, and interpersonal communication. Subsequently, the association of three ideation elements with LARC use in NTB was examined. RESULTS Multivariate analysis revealed that LARC use was higher among women with a positive attitude toward LARC and high frequency of interpersonal communication. Women with positive attitudes had 7 times greater odds of using LARC than women with negative attitudes (adjusted odds ratio [aOR] = 7.18; 95% confidence interval [CI] = 6.09–8.55). Women with a high frequency of interpersonal communication were 2.4 times more likely to use LARC than women with low communication frequency (aOR = 2.40; 95% CI = 1.94–2.99). CONCLUSIONS To increase the use of LARC in NTB, family planning programs should not only focus on improving women’s knowledge but also prioritizing the promotion of positive attitudes toward LARC and facilitating interpersonal communication.